INFLUENCE QUALITY SERVICE AND PROMOTION TO VOLUME SALE ON PT. PRIORITY RENGAT - Rusman Latief; Ika Widiastuti (Perkumpulan Dosen Program Hibah Indonesia, 2024)
The formulation of the problem studied is whether there is a simultaneous or partial influence between service quality and promotion of volume sale at PT. Priority Rengat. Objective research namely for know the influence quality service And promotions on sales volume at PT. Rengat Priority.Method study that is Quantitative methods are descriptive research regarding service quality and promotion on sales volume at PT Prioritas Rengat. H results study that is Coefficient Correlation is known that (X 1 ) quality service and (X 2 ) promotion has a positive relationship with (Y) sales volume. This can seen from mark efficiency correlation multiple R is 0.420. And furthermore tested with The coefficient of multiple determination (R 2) is 0.176. this shows that (X 1 ) quality service and (X 2 ) promotion have a variation relationship with (Y) volume sale as big as 17.6 %. And the rest 82.4 % in influence by variable besides (X 1 ) and (X 2 ). Based on the significant value seen in the sig column, namely 0.009 means the probability of 0.009 is smaller than 0.05. This means it has a greater influence significant between quality service And promotions on sales volume